Specification of a social network-based PHR. (2nd August 2019) - Tanhapour, Mozhgan; Safaei, Ali Asghar
Institute of Medicine (IoM) has introduced the patient-centred care as one of the six aims to improve healthcare quality. Personal health record (PHR) systems play a key role for employing patient-centred care. Also, there is increasing tendency to use Web 2.0 services in healthcare. Using a descriptive study, this paper specifies a social network-based PHR named health social network-personal health record ( HSN - PHR ). First a hybrid PHR model is proposed which provides an integrated viewpoint of individual's health information. It contains reliable information both for patients and healthcare providers although it is fully controlled by its owners. The requirements of developing a hybrid PHR model in a health social network are elicited and specified in IEEE Std 830-1998 standard format. The requirements are elicited using observation, introspection and questionnaire. Development of such social networking-based PHR system can improve personal and public health level in the society.